Determining the Optimum Irrigation Schedule in Furrow Irrigated Cotton using Soil Moisture Sensors. Issue 1 (21st February 2019) - Plumblee, Michael T.; Dodds, Darrin M.; Krutz, L. Jason; Catchot, Angus L.; Irby, J. Trenton; Jenkins, Johnie N.
Abstract : Core Ideas: A sensor threshold of –90 kPa resulted in net returns that were 142/acre greater than the producer standard. A sensor threshold of –90 kPa increased IWUE at least 61% relative to ‐50 and ‐130 kPa thresholds. Neither increasing nor decreasing the threshold as a function of growth stage improved yield relative to a season‐long threshold of –90 kPa. The Mississippi River Valley Alluvial Aquifer (MRVAA) is declining at a rapid rate due to withdrawal for agricultural irrigation. This research was conducted to develop a sensor‐based irrigation threshold for cotton (Gossypium hirsutum L.) that maximizes net returns and irrigation water use efficiency (IWUE). The effects of irrigation based on growth stage (full season, emergence to first bloom, first bloom to peak bloom, and peak bloom to first cracked boll) and irrigation threshold (non‐irrigated, –50 kPa, –90 kPa, and –130 kPa) on cotton lint yield, net returns above irrigation costs, and IWUE were evaluated on a Leeper silty clay loam (fine, smectitic, nonacid, thermic Vertic Epiaquepts). Net returns above irrigation costs were 142/acre greater when the threshold was maintained at –90 kPa rather than –50 kPa (p < 0.0001). Maintaining the threshold at –90 kPa also increased IWUE at least 61% relative to the –50 and –130 kPa thresholds (p < 0.0001). Neither increasing nor decreasing the threshold as a function of growth stage improved yield relative to a season–long threshold of –90 kPa (p = 0.5460). Our data indicate that yield, net returns above irrigation costs, and IWUE are maximized by maintaining a season‐long threshold of –90 kPa. Adoption of this technique could reduce agriculture withdrawal from the MRVAA and thus improve its sustainability.